Research on Robust Model Predictive Control for Electro-Hydraulic Servo Active Suspension Systems - Wang, Dazhuang; Zhao, Dingxuan; Gong, Mingde; Yang, Bin (IEEE access, 2018)
The suspension system is an important component of any vehicle as it transmits the force and torque between the wheel and the frame, satisfying the requirements of ride comfort and handling stability. To solve the problem of active suspension control, a seven-degree-of-freedom active suspension system model with electrohydraulic actuators is established. Through the approximate expansion in the rolling time domain, a robust model predictive controller (RMPC) for the active suspension system is designed and the RMPC of the active suspension is deduced by defining the RMPC performance evaluation function. A fractional PID controller is used to control the active suspension hydraulic actuators. The accuracy and efficiency of the controller are verified with prototype vehicle simulations and road experiments. Results show that the performance of the active suspension system is better than that of traditional suspension systems. The ride comfort and handling stability are considerably improved by the reductions of vertical acceleration, pitch angle, and roll angle accelerations.